Feminism in Indian English Literature: Exploring the Influence of Women's Rights Advocacy in Indian English Literature (Journal of Advances and Scholarly Researches in Allied Education, 2018)
“When women are the advisor, the Lord of creation don’t take the advice, till they have persuaded themselves that it is just what they intended to do, then they act upon it and if it succeeds , they give the weaker vessel half the credit of it if fails, they generously give herself the whole. ” These are the quotes of America’s treasured novelist and author of Little Women, an outspoken, a woman who showed grit and determination and an early women suffrage supporter. It can even be the muttering voice behind the screens in almost every household around the world.